LA ETIMOLOGÍA EN EL DICCIONARIO DE LA LENGUA - Miranda, Félix Bugueño (Revista Letras, 2004)
A informação etimológica parece ser uma questão secundária em muitos dicionários da língua. O presente trabalho almeja demonstrar que o comentário etimológico não está relacionado unicamente com o signo-lema como significante, mas como significado também. Etymology in the language dictionary Abstract The etymological information seems to have no important place in the microstructure of a large number of monolingual dictionaries. This paper aims to demonstrate that the etymological information is related not only with the formal comment of the microstructure, but with de semantic comment too.